(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
As the not-so-new-now coronavirus pandemic has affected all walks of life, education has not been an exemption; what is more, it is one of the most severely hit sectors. The unknown crisis created unprecedented circumstances for all participants in the education process, and school leaders have had a double job: to navigate their institutions and to look after their employees. The latter is a pretty delicate task - they have had to keep doing business and running their companies while minding the language since physical distancing necessitated the use of electronic communication, thus making room for vagueness and even misinterpretations. Ten education leaders of primary and secondary schools in North Macedonia have been video-interviewed on everyday COVID-19-related situations from their workplace context. Discourse completion tasks (DCTs) have been employed as a data elicitation method. Being given the open-ended, only topically specified scenarios, the respondents are asked to recreate their language reaction to situations that have happened in their newest pandemic work life. The interviews have been transcribed, and the leaders’ language choices have been analyzed. The findings show that, luckily, the leaders have been mindful about their words and have mostly chosen to use positive, calm, and encouraging language.